Repressive Interactions Between Transcription Factors Separate Different Embryonic Ectodermal Domains - Klein, Steven L.; Tavares, Andre L. P.; Peterson, Meredith; Sullivan, Charles H.; Moody, Sally A. (Frontiers in Cell and Developmental Biology, 2022)
The embryonic ectoderm is composed of four domains: neural plate, neural crest, pre-placodal region (PPR) and epidermis. Their formation is initiated during early gastrulation by dorsal-ventral and anterior-posterior gradients of signaling factors that first divide the embryonic ectoderm into neural and non-neural domains. Next, the neural crest and PPR domains arise, either via differential competence of the neural and non-neural ectoderm (binary competence model) or via interactions between the neural and non-neural ectoderm tissues to produce an intermediate neural border zone (NB) (border state model) that subsequently separates into neural crest and PPR. Many previous gain- and loss-of-function experiments demonstrate that numerous TFs are expressed in initially overlapping zones that gradually resolve into patterns that by late neurula stages are characteristic of each of the four domains. Several of these studies suggested that this is accomplished by a combination of repressive TF interactions and competence to respond to local signals. In this study, we ectopically expressed TFs that at neural plate stages are characteristic of one domain in a different domain to test whether they act cell autonomously as repressors. We found that almost all tested TFs caused reduced expression of the other TFs. At gastrulation these effects were strictly within the lineage-labeled cells, indicating that the effects were cell autonomous, i.e., due to TF interactions within individual cells. Analysis of previously published single cell RNAseq datasets showed that at the end of gastrulation, and continuing to neural tube closure stages, many ectodermal cells express TFs characteristic of more than one neural plate stage domain, indicating that different TFs have the opportunity to interact within the same cell. At neurula stages repression was observed both in the lineage-labeled cells and in adjacent cells not bearing detectable lineage label, suggesting that cell-to-cell signaling has begun to contribute to the separation of the domains. Together, these observations directly demonstrate previous suggestions in the literature that the segregation of embryonic ectodermal domains initially involves cell autonomous, repressive TF interactions within an individual cell followed by the subsequent advent of non-cell autonomous signaling to neighbors